That's good reasoning, what about x>0 then? In case of x=0 is obvious
I start by repeating what I wrote in post # 12
[math]y(x) = 3x^6+4x^5-6x^3+3 \implies y' = 18x^5 + 20x^4 - 18x^2.[/math]
[math]a(x) = (3x^6 - 6x^3) \text { and } b(x) = 4x^5 + 3 \implies\\ a + b = y.[/math]
[math]a' = 18x^5 - 18x^2 = 18x^2(x^3 - 1) \implies a > - 3 \text { if } x \ne 1 \text { and } a(1) = - 3.[/math]
[math]b(0) = 3 \text { and } b > 3 \text { if } x > 0.[/math]
[math]y(0) = 3 > 0, \ y(1) = 4 > 0.\\
0 < x < 1 \implies b > 3 \text { and } a > - 3 \implies y = a + b > 0.\\
1 < x \implies b > 7 \text { and } a > - 3 \implies a + b > 4 > 0.[/math]
[math]\therefore x \ge 0 \implies y > 0.[/math]
[math]b' = 20x^4 > 0 \text { if } x \ne 0 \text { and } b'(0) = 0 \implies\\
b \text { is monotonically increasing.}[/math]
[math]x < 0 \implies a > 0. \\ b \left ( \left \{ - \dfrac{3}{4} \right \}^{1/5} \right ) = 0.\\ \left ( - \dfrac{3}{4} \right )^{1/5} \le x < 0 \implies y > 0.[/math]
Putting that together with the previous result, we have
[math]\left ( - \dfrac{3}{4} \right )^{1/5} \le x \implies y > 0.[/math]
At this point we need a different decomposition of y.
[math]c(x) = 4x^5 - 6x^3 = 2x^3(2x^2 - 3) \text { and } d(x) = 3x^6 + 3 \implies c + d = y.[/math]
[math]x = - \sqrt{\dfrac{3}{2}} \implies c = 0 \text { and } - \sqrt{\dfrac{3}{2}} < x < 0 \implies c > 0.[/math]
[math]\text {But } d \ge 3 \text { for all } x \implies y \ge 0 + 3 > 0 \text { if } - \sqrt{\dfrac{3}{2}} < x < 0.[/math]
Putting that together with the previous result, we have
[math]- \sqrt{\dfrac{3}{2}} \le x \implies y > 0.[/math]
I am running out of time here. Do you see the last step? Give it a go. I'll be back in an hour or two.